Degradation assessment of waterlogged wood at Haimenkou site (Fracture and Structural Integrity, 2014)
Haimenkou site is the largest railing-enclosed wooden architecture settlement site on the waterfrontin current China. This research conducts degradation assessment of waterlogged wood at Haimenkou site withvarious methods, including maximum moisture content analysis, basic density analysis, shrinkage measurement,swelling analysis, chemical composition analysis, measurement of compression strength parallel to grain, SEMmicrostructure analysis and measurement of crystallinity, providing scientific guidance for the subsequentformulation of proper methods of reinforcement.
Keywords: Degradation assessment